The archive that writes itself: tracing the roots of solipsistic sound culture in the digital age - Frisk, Henrik (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 2018)
In artistic research the question of how to document the artistic practice that is the focus of the research is important, but largely unresolved. This paper discusses the various ways in which the materiality of the artistic practice may be represented in different forms for documentation. Identified as a twofold processes in which it is first necessary to identify which kind of data might represent the materiality of the artistic process and, then, to work out methods to document it, a number of different systems for documenting music is discussed. The particular case of open form compositions is introduced as an example of how aesthetic perspectives must influence the recording of the artistic process. The notion of the personal archive is further considered as a tool that allows for reflection and introspection, and leads to a discussion concerning different analogies of writing, and of perception as a form for writing. Artistic practice is a complex activity for which there will never be one universal method for documentation, and a preliminary conclusion is drawn that it is not in the structurality of the data that the potential lies, but in the way the different layers generated by the process are interconnected. Deconstructing the roles of the writer, the reader and the different notions of writing may widen the perspective and prevent the archive from restructuring and continuously narrowing down what may be seen as valid data in the materiality of artistic practice.